Congenital Microstomia in a Neonate with Impending Respiratory Compromise. (28th December 2014) - Nguyen, Khoa N.; Semenov, Igor; Blasiole, Brian; Robison, Jacob G.; Chi, David H.
Abstract : Microstomia is the term used to describe a reduction in the size of the oral aperture that is severe enough to compromise quality of life, nutrition, and cosmesis. Few cases of congenital microstomia have been reported as most microstomia cases are due to burn injuries. We are presenting a case of a neonate who was found to be in respiratory distress with severe congenital microstomia from no known cause. This case illustrates the rarity of this type of pathologic anatomy as well as the teamwork and tools necessary to treat these patients.